Hubungan Antara Lama Menderita Diabetes Melitus Tipe 2 Dengan Kejadian Peripheral Arterial Disease Pada Pasien Diabetes Melitus Tipe 2 Di Puskesmas Kedaton Kota Bandar Lampung - Adinda Ayu Lintang S; Hanna Mutiara; Merry Indah Sari; Muhartono; Ryan Falami (CV. Jasa Sukses Abadi, 2019)
Diabetes mellitus is a metabolic disease with characteristics of hyperglycemia occurs due to abnormalities of insulin secretion, insulin function, or both. Diabetes mellitus causes various kinds of complications, one of which is peripheral arterial disease (PAD). PAD is is a condition characterized by atherosclerotic occlusive disease of the lower extremities. The purpose of this study to knowing the relationship between the length of suffering type 2 diabetes mellitus and the incidence of peripheral arterial disease (PAD) in patients with type 2 diabetes mellitus in Puskesmas Kedaton Kota Bandar Lampung. This research is correlative analytic with cross sectional approach. The study was conducted November 2017. The population in this study were all patients with DM type 2 who joined prolanis activities at Puskesmas Kedaton of Bandar Lampung city. The number of research samples are 40 respondents with consecutive sampling technique. This results has 17 male and 23 women respondents. The average duration of DM is 9.8 years. Respondents with normal were 52.5%, mild PAD 12.5%, moderate 32.5% and severe 2.5%. Spearman test results of both variables obtained p value of 0.001 and correlation value 0.651. The conclusion is there are relationship between length of suffering type 2 diabetes mellitus and the incidence of peripheral arterial disease (PAD) in patients with type 2 diabetes mellitus in Puskesmas Kedaton of Bandar Lampung city.